Chemical analyses of Egyptian mummification balms and organic residues from storage jars dated from the Old Kingdom to the Copto-Byzantine period. (September 2017) - Łucejko, Jeannette; Connan, Jacques; Orsini, Sibilla; Ribechini, Erika; Modugno, Francesca
Abstract: Twenty three samples of Egyptian organic materials, spanning from the Old Kingdom to the Copto-Byzantine Period, were investigated by gas chromatography-mass spectrometry. The sample set was comprised of ten balm samples from human mummies, three balms from shrews, and ten samples of residues scraped from jars and amphora from storehouses. This research program was undertaken with two main goals: Firstly to provide complementary data on the mummification balms from both humans and animals with an emphasis on the occurrence of bitumen in mummification mixtures. Secondly to explore whether the jar residues were mixtures that were used for mummification purposes or whether they were pure ingredients stored for various uses including ritual practices. The analysis highlighted that the most abundant constituents of the mummification balms were: fats or oils, waxes, conifer resin, pitch, mastic resin, castor oil, and bitumen. Balms from animal mummies were not found to be significantly different from the balms from human mummies. Residues from potsherds appeared to belong to two categories: pure products (fats and castor oil) and mixtures containing fats, Pinaceae resin and pitch, mastic resin, and castor oil, i.e. the constituents also identified in mummification balms. The mixtures were thus residues of preparations for ritual practices and embalming. This study demonstrates that bitumen is underestimated by the chemical approach currently applied in most archaeometric studies of Egyptian organic residues, which are better suited for the identification of lipids and resinous materials. We thus applied a specific analytical design, targeted at bitumen. Bitumen from the Dead Sea was conclusively identified using as reference materials for comparison, i.e. the present day bitumen from the Dead Sea floating blocks, as well as several bitumens from mummification balms and bitumen lumps unearthed from the archaeological site of Tell Yarmouth near Jerusalem in Israel. Highlights: Egyptian embalming materials were characterised by GC/MS. Complex mixtures of lipids, resins, pitch, and bitumen were determined. A specific procedure was applied to identify the origin of bitumen.